Identifying Board Processes through Behavioral Perspective toward Corporate Governance using Meta-Synthesis Approach - Ali Divandarri (University of Tehran, 2021)
Objective: Boards are mainly concerned with communication issues as well as how to overcome the uncertainty associated with the strategic decision-making process rather than simply the old challenge of "conflict of interests" and their legal and structural solutions. In fact, although structural and legal issues are important in corporate governance, they are not sufficient for a comprehensive understanding of the process of corporate governance from a theoretical point of view and implementation of good governance in practice. That is because the interactions between the board members as well as the interactions between them and other stakeholders of the organization can play a more important role in this regard and should be the focus of attention. Therefore, this study aims to conduct a systematic review on all the articles published in the field of corporate governance using a behavioral approach in order to create a big imge for the researchers to design an appropriate conceptual model and conduct empirical research accordingly. The main question of this research is: “what concepts have been studied by the researchers in the field of corporate governance using a behavioral approach”. Methodology: The present research is based on a meta-synthesis approach. It is a qualitative appraoch to present a combination of research findings with the aim of creating a conceptual framework and summarizing the concepts in order to provide easier access for exploitation in future experimental research. The study population included all the articles related to corporate governance which have been published in the reliable international journals such as JSTORE, Emerald, Science Direct (Elsevier), Scopus, Springer, Proquest, and Wiley until the end of 2018. In the preliminary stage, 140 articles were extracted. Then, the respective abstracts were studied and those articles that did not comply with at least one of the characteristics of the behavioral approach to corporate governance were eliminated. These characteristics include: 1- they should be 1- about the service duties of the board of directors, 2- about the interactions or decisions of the board of directors and the senior management team as well as dealing with the issues such as power, trust, feelings, participation, and etc, 3- using a theoretical basis other than theory of representation, 4- about the demographic characteristics or competencies of the board members, and 5- about the board processes and their dynamics using the raw data. The Journal Impact Factor and SiteScore indicators were used in the last stage of the article screening process. Findings: After identifying 140 related articles and coding 78 selected articles with the average journal impact factor (JIF) of 4.34, 1722 content codes were registered to identify the concepts in this field. 139 concepts were identified as a result of open coding process, which were categorized into 25 subcategories and 9 main categories. Then, by performing axial and selective coding according to the grounded theory principles, the conceptual framework of "corporate governance based on a behavioral approach" was developed. The category of duties and outcomes of the board of directors including the control and service delivery task, was considered as the central category. Accordingly, the board should support and direct CEOs while keeping their distance and challenging them. The stakeholders, on the other hand, are regarded as the main trigger for the board duties. In fact, the external stakeholders as well as the internal stakeholders expect the board to be accountable and create value that can lead them to perform control or service tasks. On the other hand, the structure of the board as well as the demographic characteristics and competencies of the board members are considered as the intervening variables. In other words, there is a relationship between the structure of the board as well as the demographic characteristics and competencies of the individuals. In addition, the underlying conditions, depending on the contextual factors of corporate governance, can cause distinct changes in research variables in different research environments and are different from the intervening factors. In a conceptual framework, the underlying factors are divided into three levels of: company, industry, and macro (national). These factors affect the board processes. Moreover, the action and reaction strategies are the events that are performed by the actors during performing the board tasks. These strategies begin from the first moment the board performs its duties and continue until the organizational goals are achieved. Finally, the board tasks will result in organizational consequences including financial consequences, strategic changes of the organization, as well as social performance consequences for the organization, which is considered as the result within the conceptual framework. Conclusion: The researchers should move away from the control tasks of the board of directors and pay more attention to the service tasks including the participation in the organizations strategies. They should also investigate the impact of underlying factors such as corporate ownership structure as well as environmental uncertainty on power relations. In addition to demographic factors, it can highlight the competencies of the board as well as human and communication capital and their role in the quality of the decisions. They should also develop contingency models that provide a more comprehensive explanation of the dynamics of the boards through studying cognitive, emotional, and behavioral processes as well as paying attention to different factors such as power, trust, and feelings.